Hemophagocytic Syndrome in a Patient with Adult-onset Still’s Disease - Yalkın ÇALIK; Safinaz ATAOĞLU; Ersun BAŞ; Selma YAZICI; Ali Erdem BAKİ and Metin YAVUZ (Archives of Rheumatology, 2011)
Hemophagocytic syndrome is a fatal and life-threatening syndrome characterized by pancytopenia and multiple organ failure. It can frequently be seen in childhood as a primary or familial condition. In adults, it occurs secondarily. In etiology, wide range of factors are related to this syndrome. Adult-onset Still’s disease seems to be one of the systemic rheumatological diseases that cause this syndrome. In our literature review, we found few studies related to this syndrome. In this article, we report a 40-year-old female patient who had been treated with the diagnosis of Adultonset Still’s disease for four years in our clinic and who developed hemophagocytic syndrome during her follow-ups.